Analisis Kemampuan Membaca Lancar Level I di Sekolah Dasar - Atthahirah Azzahra; Mira Maulidya Fajar; Sukma Rabbani; Chandra Chandra; Ari Suriani (Pusat Riset dan Inovasi Nasional, 2024)
This study focuses on analyzing the fluency reading ability of elementary school students, particularly first-grade students. Fluency reading proficiency is a fundamental skill crucial for elementary school students as it serves as a foundation for further reading development. Fluency reading entails the ability to read a text accurately and with appropriate intonation, allowing the reader to comprehend both the explicit and implicit messages conveyed by the author. Reading fluency is associated with the accuracy of word recognition and the ease of word recognition. Additionally, fluency reading encompasses reading at an appropriate pace, clear pronunciation, and good comprehension. This research has significant implications for analyzing and evaluating the fluency reading skills of first-grade elementary school students. The findings can be utilized to develop appropriate strategies and interventions to enhance fluency reading skills during the early years of primary education, thereby laying the groundwork for students' academic development in the future.